2017
DOI: 10.24294/ti.v1.i2.51
|View full text |Cite
|
Sign up to set email alerts
|

SAPHO syndrome in which certolizumab pegol was effective: A case report

Abstract: A 45-year-old male suffered from persistent swelling and redness, with pain in his left lower leg and ankle. Pathological findings isolated from the ankle joint by arthroscopic synovectomy showed mild synovitis. Initially, this case was diagnosed as chronic mild arthritis and later treated as phlegmon because of the persistent redness and swelling inflammatory findings in his left lower leg. A systemic survey was performed. Based on the findings-such as chronic ankle arthritis with ipsilateral plantar pustulos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…Other treatments included glucocorticoids, bisphosphonates, antirheumatic drugs, and TNF inhibitors 14 . In one of our previous case reports, we found that the TNF inhibitor certolizumab pegol is effective, which showed significant improvements in skin symptoms, physical findings, and laboratory findings in 6 weeks of treatment 16 …”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Other treatments included glucocorticoids, bisphosphonates, antirheumatic drugs, and TNF inhibitors 14 . In one of our previous case reports, we found that the TNF inhibitor certolizumab pegol is effective, which showed significant improvements in skin symptoms, physical findings, and laboratory findings in 6 weeks of treatment 16 …”
Section: Discussionmentioning
confidence: 75%
“…14 In one of our previous case reports, we found that the TNF inhibitor certolizumab pegol is effective, which showed significant improvements in skin symptoms, physical findings, and laboratory findings in 6 weeks of treatment. 16 In recent years, there has been remarkable progress in the treatment of PPP. The biological.…”
Section: Discussionmentioning
confidence: 99%
“…However, further investigation is required. Although recent reports have emphasized the efficacy of biologics that target inflammatory cytokines such as antibodies to interleukin-1β and tumor necrosis factor-α [5,6] , use of these agents remains uncovered by health insurance in Japan, showing unresolved discrepancy in practical use for clinicians. Conversely, several trials of various treatments have been reported, including corticosteroids, immunosuppressant, and antibiotics, and the efficacy of the combination of corticosteroids and immunosuppressants remains equivocal.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, papers have introduced various autoinflammatory diseases [1,2] . Recently, the concept of these diseases has expanded, and intractable psoriasis, severe acne, and similar related diseases are occasionally included in this disease entity [3][4][5][6][7] .…”
mentioning
confidence: 99%